Development of syllabox media using syllabic methods to improve informative text reading ability students: - Nur Adila binti Baodin; Panca Dewi Purwati (Jurnal Prima Edukasia, 2026)
This research aims to develop, test the feasibility, and effectiveness of Syllabox media based on syllabic methods to improve the reading ability of informative texts for class II students at SDN Pandeanlamper 03. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects were class II students who were involved in small-scale and large-scale trials. Data collection techniques include observation, interviews, questionnaires, documentation, as well as pretest and posttest. The results of material expert validation show a feasibility level of 98.33% and media expert validation of 93% with a very feasible category. The results of the effectiveness test show a significant increase in the ability to read informative texts, proven through the paired sample t-test and the N-Gain value in the medium category. Thus, the Syllabox media based on syllabic methods was declared feasible and effective for improving the ability to read informative texts in class II elementary school students.